Populerization of maize among the small farmers of Ernakulam district of Kerala through front line demonstration - Vijendra Kumar Meena; Shinoj Subramannian; Pushraj Anjlo and Dipti N.V (Indian J. Agric. Res., 2015)
To popularise maize crop (Zea maize) among small farmers of Ernakulam district of Kerala, Krishi Vigyan Kendra, ICAR- Central Marine Fisheries Research Institute organised 25 demonstrations during 2012-13 to 2014-15 on traditional farmer’s field. Maize cultivars Pratap-4 and Pratap-5 were used for demonstration during January to May and September to December season. Farmers were motivated and trained for maize seed multiplication and cultivation aspects. Results of demonstration revealed that Pratap-4, Pratap-5 and local variety produced 33.70, 30.7 and 23.4 q/ha, respectively. Average income generated by the crop range from Rs. 40440/- to Rs. 36840/- and local variety Rs. 30240/-. Cost benefit ratio was 2.18, 1.99 and 1.77. for Pratap-4 , Pratp-5 and local variety, respectively. Technology index was reduced in the 2nd and 3rd year showed the feasibility of maize crop in the area. Thereafter, 500 farmers initiated the small scale farming of maize in the district with the technical guidance provided from KVK.